1989
DOI: 10.1080/01419870.1989.9993651
|View full text |Cite
|
Sign up to set email alerts
|

Business strategies among East Indian entrepreneurs in Toronto: The role of group resources and opportunity structure

Abstract: This article examines the class and ethnic resources used by East Indian immigrants in self-owned enterprise and the opportunity structure within which they operate. A non-probability sample (N=38) of East Indian entrepreneurs in Toronto is the primary data source. Major findings attest to an individualistic business strategy employed by these entrepreneurs in which class resources are more consequential than ethnic networks or communal ties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…Market conditions are commonly perceived to determine business access and development for immigrants. The few extant studies emphasize the appropriateness of the social embeddedness approach (Bauder ; Chan and Cheung ; Dalziel ; Hiebert ; Marger ; Teixeira , ; Teixeira, Lo, and Truelove ) although a few recent studies have hinted at the appropriateness of mixed embeddedness (Hiebert , ; Ley , ). However, as suggested earlier, these studies have two limitations.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…Market conditions are commonly perceived to determine business access and development for immigrants. The few extant studies emphasize the appropriateness of the social embeddedness approach (Bauder ; Chan and Cheung ; Dalziel ; Hiebert ; Marger ; Teixeira , ; Teixeira, Lo, and Truelove ) although a few recent studies have hinted at the appropriateness of mixed embeddedness (Hiebert , ; Ley , ). However, as suggested earlier, these studies have two limitations.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…The role of contextual factors such as the influx of immigrant population and offshore capital in the creation of the ethnic sub-economy was also confirmed in a study of Chinese businesses in Richmond, British Colum bia (Li, 1992). A study of East Indian entrepreneurs in Toronto also found that although ethnic networks and communal ties were important in the development of business strategies, their effect was not as consequential as class resources (Marger, 1989). However, another study of ]halo-Canadian-owned construction businesses inVancouver found that family-based and ethnically based economic strategies facilitated growth in ownership in construction and construction materials businesses (Walton-Roberts & Hiebert, 1997).…”
Section: Ethnic Enclave Economymentioning
confidence: 99%
“…Education, capital start-up, previous experience, and parental occupation (class resources) have been found to be more important in business success than ethnic involvement (Marger 1989), while highly successful entrepreneurs have been found to make less use of social capital (Shin and Han 1990). Others have analysed the relative contribution of immigrants to entrepreneurial activity in their host country (Light and Rosenstein 1995;Kim et al 2003;Hammarstedt 2001;Levie and Smallbone 2006).…”
Section: Entrepreneurial Regions In Motionmentioning
confidence: 99%